Α‐Lipoic acid up‐regulates gene expression but reduces protein levels of fibroblast growth factor 21 in HepG2 cells. Issue 4 (20th July 2022) - Zhang, Xiaochun; Zhao, Yanyan; Liang, Xiangyan; Zhang, Lijun; Li, Ke; Sun, Zhuo; Zhao, Yu‐Feng
Abstract: Fibroblast growth factor 21 (FGF21) is a metabolism‐regulating hepatokine, and its expression is finely controlled by the nutrients and cellular stressors. α‐Lipoic acid (ALA) regulates fuel metabolism as a nutrient, but it also arouses mitochondrial and endoplasmic reticulum (ER) stress as well as oxidative stress in hepatocytes. However, the role of cellular stress in ALA‐regulated FGF21 expression has not been demonstrated as yet. The present study found that ALA up‐regulated FGF21 gene expression while it reduced FGF21 protein levels in HepG2 cells, which was accompanied by mitochondrial damage that was shown by ATP reduction and ROS elevation. ALA led to mitochondrial stress and ER stress as shown by the increased expression of HSP60, ATF6 and ATF4. Inhibition of ER stress by 4‐PBA significantly attenuated ALA‐stimulated FGF21 gene expression while it did not influence the reduction of FGF21 protein levels. H2 O2 ‐induced oxidative stress reduced FGF21 protein levels in HepG2 cells, and anti‐oxidation by Tempol blocked ALA‐induced reduction of FGF21 proteins. In conclusion, ALA up‐regulates FGF21 gene expression through the stimulation of mitochondrial and ER stress while it reduces FGF21 protein levels through the induction of oxidative stress in HepG2 cells. Further studies are needed to demonstrate the in vivo effect of ALA on hepatic FGF21 expression.